A new bacterial blight resistance gene Xa50(t) in the Xa4 locus confers resistance against Xanthomonas oryzae pv. oryzae in rice - Li, Man; Shafique, Muhammad Sohaib; Zhou, Houyu; Wang, Jialu; Liu, Yapei; Wang, Chunlian; Wang, Zhonghua; Ji, Zhiyuan (Frontiers in Plant Science, 2025)
Rice bacterial leaf blight (BB), caused by Xanthomonas oryzae pv. oryzae (Xoo), leads to severe yield losses in rice. Resistance breeding is a sustainable approach to mitigate the impact of this disease. In this study, a novel BB resistance gene, Xa50(t), was identified in the germplasm line CX315. Genetic analysis revealed that the resistance is conferred by a dominant resistant gene, tentatively named Xa50(t), which provides broad-spectrum and robust resistance to multiple Xoo strains. Using an F2 population derived from a cross between CX315 and IR24, Xa50(t) was fine-mapped to a 147.7 kb region on the long arm of chromosome 11 flanked by InDel markers M11–588 and M11-602. Gene expression analysis identified three candidate genes out of 13 open reading frames (ORFs) predicted in candidate region. ORF5 and ORF9 (Xa4), encoding a wall-associated kinase (WAK)-like protein, and ORF13, encoding a receptor-like kinase protein, were significantly upregulated in CX315 following Xoo inoculation. While ORF9 is predicted to encode the Xa4 resistance gene, CRISPR/Cas9-based knockout of Xa4 did not abolish Xa50(t)-mediated resistance in the CX315 line, indicating that Xa50(t) confers resistance in a complementary manner. Transcriptome analysis further revealed that oxidative stress response and immune signaling pathways were enriched in CX315 at 48 hours post-inoculation. Together, these findings highlight the potential of Xa50(t) as a valuable genetic resource for improving BB resistance in rice, and the transcriptome data provides molecular insight into the BB resistance response.